Anterior and Posterior Corneal Astigmatism after Refractive Lenticule Extraction for Myopic Astigmatism - Kazutaka Kamiya; Kimiya Shimizu; Mayumi Yamagishi; Akihito Igarashi; Hidenaga Kobashi (Journal of Ophthalmology)
Purpose. To assess the amount and the axis orientation of anterior and posterior corneal astigmatism after refractive lenticule extraction (ReLEx) for myopic astigmatism. Methods. We retrospectively examined 53 eyes of 53 consecutive patients (mean age ± standard deviation, 33.2 ± 6.5 years) undergoing ReLEx to correct myopic astigmatism (manifest cylinder = 0.5 diopters (D)). Power vector analysis was performed with anterior and posterior corneal astigmatism measured with a rotating Scheimpflug system (Pentacam HR, Oculus) and refractive astigmatism preoperatively and 3 months postoperatively. Results. Anterior corneal astigmatism was significantly decreased, measuring 1.42 ± 0.73 diopters (D) preoperatively and 1.11 ± 0.53 D postoperatively (p<0.001, Wilcoxon signed-rank test). Posterior corneal astigmatism showed no significant change, falling from 0.44 ± 0.12 D preoperatively to 0.42 ± 0.13 D postoperatively (p=0.18). Refractive astigmatism decreased significantly, from 0.92 ± 0.51 D preoperatively to 0.27 ± 0.44 D postoperatively (p<0.001). The anterior surface showed with-the-rule astigmatism in 51 eyes (96%) preoperatively and 48 eyes (91%) postoperatively. By contrast, the posterior surface showed against-the-rule astigmatism in all eyes preoperatively and postoperatively. Conclusions. The surgical effects were largely attributed to the astigmatic correction of the anterior corneal surface. Posterior corneal astigmatism remained unchanged even after ReLEx for myopic astigmatism.